Representation of prostitution in the novels woman at Point Zero by Nawwal el Saadawi and Nights at the Circus by Angela Carter - Khan, Nujhat Jahan (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2019.